Financial and Economic Tools Used in the World Hospitality Industry : Proceedings of the 5th International Conference on Management and Technology in Knowledge, Service, Tourism & Hospitality 2017 (SERVE 2017), 21-22 October 2017 & 30 November 2017, Bali, Indonesia & Moscow, Russia /: Proceedings of the 5th International Conference on Management and Technology in Knowledge, Service, Tourism & Hospitality 2017 (SERVE 2017), 21-22 October 2017 & 30 November 2017, Bali, Indonesia & Moscow, Russia. (2018) - Unknown
No abstract available